THE EFFECTIVENESS OF PROBLEM-BASED LEARNING (PBL) MODELS BASED ON SOCIO-SCIENTIFIC ISSUES (SSI) TO IMPROVE THE ABILITY OF SCIENCE LITERACY ON CLIMATE CHANGE MATERIALS - Putri, Pungky Dilaka; Tukiran, Tukiran; Nasrudin, Harun (JPPS (Jurnal Penelitian Pendidikan Sains), 2018)
This study aimed to determine the effectiveness of Problem-Based Learning (PBL) model based on Socio-scientific Issues (SSI) to improve the ability of science literacy on climate change materials. This type of research is a 4-D model development with research design using One Group pretest-posttest design. Subjects in this study are learning devices IPA with PBS model based on SSI which is tested in this II test phase in grade VII students at SMP Negeri 1 Bangsal Mojokerto as many as 3 classes. The technique of data analysis for the result of science literacy test in learning is data of pre-test result and post-test of student that function to know improvement of science literacy of student before and after learning. This increase is known through N-Gain analysis. Based on the results of the research, it can be concluded that the learning tools of IPA with Problem Based Learning (PBL) model based on Socio-scientific Issues (SSI) to improve scientific literacy ability on climate change material developed has been effective so it is feasible to be used in learning